Enhancement of surface hardness and roughness of HQ 805 steel using diamond-like carbon coating deposited by PVD - Pakpahan, Binsar Maruli Tua; Yaqin, Rizqi Ilmal; Waluyo, Bakti Dwi; Zulfikram, Zulfikram; Mendoza, Muhammad Dominique (Jurnal Polimesin, 2025)
Diamond-Like Carbon (DLC) coatings are well-regarded for their high hardness, low friction coefficient, and excellent wear resistance, making them suitable for enhancing surface properties in demanding industrial applications. This study aims to analyze the effect of DLC coating on HQ 805 steel, focusing on improvements in surface hardness and surface roughness. HQ 805 steel, which is known for its mechanical durability, was coated using the Physical Vapor Deposition (PVD) method to achieve a uniform and adherent thin film. Hardness was evaluated using the Vickers microhardness test, while surface roughness was measured with a profilometer. Results showed a significant increase in surface hardness, with the coated samples achieving up to 798 VHN. It represented a 25–30% increase compared to the uncoated steel at 355 VHN. Surface roughness exhibited only a slight increase (5–7% Ra), indicating the thin layer and uniform deposition achieved with DLC without adversely affecting the surface finish. These results confirm that PVD-applied DLC coatings can effectively enhance the mechanical surface performance of HQ 805 steel without compromising surface quality. The optimal coating condition was found at 400°C for 4 hours. This research shows the potential application of DLC-coated HQ 805 steel in high-wear industrial environments extending component service life and improving operational efficiency.